Utilization of NodeMCU ESP8266 and RFID Technology as Recognition of Teacher Honors - Heri Wiranto; Arip Solehudin; Agung Susilo Yuda Irawan (UPT P2M State Polytechnic of Malang, 2020)
Internet of Think or so-called IoT is a technology used in all fields, one of which is in the field of school administration. The administration of SMK Sunan Gunung Jati works to manage various data such as the recording of teacher salaries and many others. With a lot of work done by the administration, the researchers utilize nodemcu esp8266 and RFID technology as a recording of teacher salaries. The methodology used is the Software Development Life Circle (SDLC) method with the waterfall model, this is in accordance with the short stages of system use. The results of this study in the form of the creation of an ID card sensor tool product that is integrated with the teacher honorarium recording application to help administrative staff manage teacher honor data and the results of testing this sensor device with 5 ID cards also indicate that the tool is able to read ID cards with a distance of 1- 2 cm.